Modelling and integrated assessment of the ecosystem services in the Mar Chiquito Reserve, Argentina (Huellas, 2018)
The methodological integration of different values in relation to the ecosystem services (ES) is a methodological challenge to be solved. This paper aims at integrating market and cultural values associated with the ES which can be found in the Mar Chiquita Biosphere reserve in the southeast of the province of Buenos Aires.This methodological approach allowed us to identify and assess the local benefits of the wetland, and to detect that they are equal to the budgetary allocation in social services such as health care, education, and the promotion of tourism of the homonymous municipality.
Keywords: wetland; ecosystem services (ES); economic assessment; methodological integration